Digital Inclusive Finance and Regional Economic Resilience: Evidence From 279 Cities in China - Ziyun Wang; Hanbin Chen (IEEE Access)
Using the panel data of 279 prefecture level cities in China from 2011 to 2022, this paper analyzes the mechanism and spatial spillover effect between digital Inclusive Finance and economic elasticity. Firstly, the relationship between digital inclusive finance and economic resilience is initially explored through benchmark regression, and regional differences are revealed through heterogeneity analysis. Secondly, the spatial effects of digital inclusive finance are investigated using the spatial Durbin model. Finally, the moderating effect model and threshold effect model is used to analyze the linear and non-linear effects of mechanism variables in the role of digital inclusive finance on economic resilience. The study shows that digital inclusive finance has a significant positive impact on enhancing economic resilience, and the impact is heterogeneous. Moreover, the positive influence of digital inclusive finance on economic resilience has spatial spillover effects. The moderating and threshold effects show that the financial market environment, industrial structure transformation and upgrading, and government intervention are important factors affecting the impact of digital inclusive finance on economic resilience. Finally, based on the research results, we propose policy recommendations aimed at effectively promoting digital inclusive finance and economic resilience in China.